IMPLEMENTATION OF ISLAMIC EDUCATION CURRICULUM DEVELOPMENT IN INTEGRATED ISLAMIC SCHOOLS IN SOUTHEAST SULAWESI - Obaid, Muh. Yahya; Safrudin, Moh; La Fua, Jumarddin; Fatimah K., St.; Hardiana, Waode; Rauf Tanaba, Sabaria (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study aims to determine the planning, implementation, and evaluation of implementing Islamic education curriculum development at integrated Islamic schools in Southeast Sulawesi. The method used in this study is qualitative research with a phenomenological approach. Data collection techniques include observation, interviews, and documentation; data is processed using data reduction, display, and verification. Data checking techniques use triangulation techniques, discussions with colleagues, and extending time in the field. The results show that the planning of the Islamic education program at integrated Islamic schools in Southeast Sulawesi is prepared at the beginning of each academic year and has been well implemented as an annual, semester, weekly, daily, enrichment, and remedial program. The curriculum implementation is carried out variably between the 2013 and independent learning curricula. Implementing the Islamic education curriculum in the classroom involves elements of educators, students, learning resources, and other supporting facilities and infrastructure. All subjects and all school activities are inseparable from the framework of Islamic teaching values. The excellence in implementing the Islamic education curriculum lies in additional activities such as Muhayyan, programmed sunnah fasting, memorization of six chosen surahs, and blessed Friday movements. The implementation of the Islamic Education curriculum can be evaluated by looking at four aspects: objectives, strategies, lesson content, and evaluation activities. Learning evaluation as a curriculum is implemented through formative, summative, and summative, with assessment targets covering cognitive, attitudinal, and skill domains.